If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-26=3/4x
We move all terms to the left:
4x-26-(3/4x)=0
Domain of the equation: 4x)!=0We add all the numbers together, and all the variables
x!=0/1
x!=0
x∈R
4x-(+3/4x)-26=0
We get rid of parentheses
4x-3/4x-26=0
We multiply all the terms by the denominator
4x*4x-26*4x-3=0
Wy multiply elements
16x^2-104x-3=0
a = 16; b = -104; c = -3;
Δ = b2-4ac
Δ = -1042-4·16·(-3)
Δ = 11008
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{11008}=\sqrt{256*43}=\sqrt{256}*\sqrt{43}=16\sqrt{43}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-104)-16\sqrt{43}}{2*16}=\frac{104-16\sqrt{43}}{32} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-104)+16\sqrt{43}}{2*16}=\frac{104+16\sqrt{43}}{32} $
| 193600x=18069333.33333 | | 35=21a | | 0.2n=5 | | -(x-1)=2(10+5x) | | -4x+6=3x+1 | | 22=3(w+6)-7w | | 22=3(w | | 6(2x+3)=12x-7 | | 8x+2(x-2)+6=10 | | -0.2(x-20)=4-x | | u+48=5u | | p+27=10p | | 12=-6n+6+6 | | 3b-4/7=2 | | 47=9+2c | | 4x+6/x=25 | | 0.4(x+6)=x/3+1 | | 9=m-6+4m | | -14x-4(2x-12)=-8 | | 20x+5=21x+1 | | (3/5)/x=3/10 | | .12m+27.95=12.95+.32m | | 4(2h+3)=3h-53 | | 15-5(4x-7)=59 | | 3/5÷x=3/10 | | c+70=6c | | 4-4.25m=42.25 | | 3/5/x=3/10 | | w+54=4w | | 4.25m+4=42.25 | | 4m+4.25=42.25 | | 4.25-4m=42.25 |